Impact of exchange rate and oil price on FDI inflows in BRICs :does volatility matter? - Foo, Lin Yie (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study investigates the effects of exchange rate volatility and oil price volatility on Foreign Direct Investment (FDI) inflows for BRICs (Brazil, Russian Federation, India and China). The testing period for this study ranges from year 1986 to 2009 for Brazil, India and China. As for Russian Federation, the sample covers the 1992 to 2009 period because of the breaking up of Union of Soviet Socialist Republics (USSR) in 1991.